2015
DOI: 10.15414/raae.2015.18.01.03-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Migrant Remittances on Farm Household Welfare in Nigeria

Abstract: International remittances are now a mechanism in development financing and a welfare strategy. Growing trends of these money transfers by migrants to their families back home in developing nations have been proven by evidences in literature and many empirical findings. This research analysed the effects of migrant remittances on the welfare of farm households in Nigeria. Welfare was measurable in terms of the households' real per capita consumption. Cross sectional data were pooled from two sources. The data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some researchers have found positive relations and some have found negative between them. A positive and significant impact of international remittances on household welfare is found by Nwaru et al (2011), Etowa et al (2015, and Akanle and Adesina (2017) while Kangmennaang et al (2018), Fatima and Qayyum (2016) Andersson (2014) found a postive relation between remittance receipt and assets accumulation of rural households. A positive and significant impact of remittances on welfare and consumer asset accumulation, especially in rural areas, but no impact on productive assets is also found.…”
Section: Key Findings Of Previous Literaturementioning
confidence: 90%
“…Some researchers have found positive relations and some have found negative between them. A positive and significant impact of international remittances on household welfare is found by Nwaru et al (2011), Etowa et al (2015, and Akanle and Adesina (2017) while Kangmennaang et al (2018), Fatima and Qayyum (2016) Andersson (2014) found a postive relation between remittance receipt and assets accumulation of rural households. A positive and significant impact of remittances on welfare and consumer asset accumulation, especially in rural areas, but no impact on productive assets is also found.…”
Section: Key Findings Of Previous Literaturementioning
confidence: 90%